Parameter Optimization of Sintering Ti-6Al-7Nb Powder and Palm Stearin Binder System for the Highest Sintered Density using the Taguchi Method / Rozie Nani Ahmad...[et al.] - Ahmad, Rozie Nani; Muhamad, Norhamidi; Wahi, Azizah; Junaidi, Syarif (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The application of titanium (Ti) based biomedical materials such as Ti-6Al-7Nb is widely being used at present. Due to the toxicity of vanadium to the human body, the Ti-6Al-7Nb alloy has been developed as a more suitable biomaterial to replace the Ti-6Al-4V alloy. The sample was prepared by a metal injection moulding process, which is a net-shaped powder metallurgy forming process using palm stearin as a binder system. Meanwhile, the Taguchi method was used in conducting the experiment of the sintering process to investigate the effects of sintering factors on the density of the sintered parts. The density measurement was carried out by the Archimedes method using distilled water as a medium. The results showed that the sintering temperatures and dwell times were the most significant parameters that contribute to the highest sintered part density.